Anterior Cruciate Ligament Revision Reconstruction. Issue 17 (1st September 2021) - Miller, Mark D.; Kew, Michelle E.; Quinn, Courtney A.
Abstract : Revision anterior cruciate ligament (ACL) reconstruction is used in patients with recurrent instability after primary ACL reconstruction. Identifying the etiology of graft failure is critical to the success of revision reconstruction. The most common etiologies include technical errors, trauma, failure to recognize concomitant injuries, young age, incomplete rehabilitation, and hardware failure. Patients should undergo a complete history and physical examination with a specific focus on previous injury mechanism and surgical procedures. A revision ACL reconstruction is a technically demanding procedure, and the surgeon should be prepared to address bone tunnel osteolysis, concurrent meniscal, ligamentous, or cartilage lesions, and limb malalignment. Surgical techniques described in this article include both single-stage and two-stage reconstruction procedures. Rates of return to sport after a revision reconstruction are lower than after primary reconstruction. Future research should be focused on improving both single-stage and two-stage revision techniques, as well as concomitant procedures to address limb malalignment and associated injuries.